Impact of Autophagy on Gene Expression and Tapetal Programmed Cell Death During Pollen Development in Rice - Hanamata, Shigeru; Sawada, Jumpei; Ono, Seijiro; Ogawa, Kazunori; Fukunaga, Togo; Nonomura, Ken–Ichi; Kimura, Seisuke; Kurusu, Takamitsu; Kuchitsu, Kazuyuki (Frontiers in Plant Science, 2020)
Autophagy has recently been shown to be required for tapetal programmed cell death (PCD) and pollen maturation in rice. A transcriptional regulatory network is also known to play a key role in the progression of tapetal PCD. However, the relationship between the gene regulatory network and autophagy in rice anther development is mostly unknown. Here, we comprehensively analyzed the effect of autophagy disruption on gene expression profile during the tapetal PCD in rice anther development using high-throughput RNA sequencing (RNA-seq). Expression of thousands of genes, including specific transcription factors and several proteases required for tapetal degradation, fluctuated synchronously at specific stages during tapetal PCD progression in the wild-type anthers, while this fluctuation showed delay in the autophagy-deficient mutant Osatg7-1. Moreover, gene ontology enrichment analyses in combination with self-organizing map clustering as well as pathway analysis revealed that the expression patterns of a variety of organelle-related genes as well as genes involved in carbohydrate/lipid metabolism were affected in the Osatg7-1 mutant during pollen maturation. These results suggest that autophagy is required for proper regulation of gene expression and quality control of organelles and timely progression of tapetal PCD during rice pollen development.